The Symbiotic Evolution of AI and Media: A Technological Leap in Knowledge Sharing and Decision-Making - Madli, Faerozh; Wahab, Mat Salleh@Salleh; Mojolou, Dean Nelson; Janin, Yuzainy; Riyard, Ag Kaifah; Lada, Suddin; Wolor, Christian Wiradendi; Kamsin, Khairunisah (Journal of Advanced Research Design, 2025)
Artificial Intelligence (AI) is more than just an innovation, it is a force reshaping how information flows through society. But how does this impact on media communication? This study uncovers the answer. AI is no longer a new or unfamiliar concept in today’s world. Its widespread use across almost every industry highlights its growing influence. AI adoption has largely had a positive impact, driven by various factors. One of the most significant is its role in information dissemination. However, the dynamics of this relationship remain unclear. This study explores the symbiotic relationship between AI and media communication, examining how AI shapes and enhances the flow of information. Additionally, this symbiotic relationship is examined in the context of a crucial global concern which is public health. The findings reveal that AI and media technology work together harmoniously to provide individuals with essential information, empowering them to make well-informed decisions more quickly. In this essence, this research highlights how AI, when integrated with media technology, serves as a powerful tool for knowledge sharing within society. Additionally, the insights from this study offer valuable implications for various stakeholders, particularly those navigating the rapid evolution of AI-driven technologies. Understanding these dynamics can help industries and policymakers maximize AI’s potential for relevance benefits.